2005
DOI: 10.1016/j.catena.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Runoff generation in an intensively disturbed, abandoned farmland catchment, Central Spanish Pyrenees

Abstract: This paper studies the hydrological response to rainstorm events of a small experimental catchment in the Central Spanish Pyrenees. The Arnás catchment was cultivated until 40 years ago, and then abandoned and affected by plant recolonisation, especially shrubs. A rainfall of a few mm is enough to produce a sudden increase in discharge, due most probably to the steep gradients and the small size of the catchment and the extensive areas with low vegetation density and thin soils. The intensity of the response s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 21 publications
4
61
1
12
Order By: Relevance
“…The complexity in the generation of runoff was also reported for several drainage basins with Mediterranean mountain climate (Gallart et al, 2002;García Ruiz et al, 2005). Llorens and Gallart (1992) and Gallart et al (1994) already showed that the response of these catchments is largely driven by antecedent conditions, demonstrating that during the year, the dominant runoff generation mechanisms change gradually, as a result of both varying catchment antecedent wetness conditions and changing rainfall event characteristics (Gallart et al, 2005).…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 65%
“…The complexity in the generation of runoff was also reported for several drainage basins with Mediterranean mountain climate (Gallart et al, 2002;García Ruiz et al, 2005). Llorens and Gallart (1992) and Gallart et al (1994) already showed that the response of these catchments is largely driven by antecedent conditions, demonstrating that during the year, the dominant runoff generation mechanisms change gradually, as a result of both varying catchment antecedent wetness conditions and changing rainfall event characteristics (Gallart et al, 2005).…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 65%
“…Long-term monitoring of these catchments has provided useful hydrogeomorphological information, enabling study of the factors that explain their hydrological and sedimentological responses Seeger et al, 2004;García-Ruiz et al, 2005;Serrano-Muela et al, 2008;Llorente-Adán et al, 2015;Nadal-Romero et al, 2016), their water and sediment sources (González et al 1997;Lana-Renault and Regüés 2009;Butzen et al, 2011;Lana-Renault et al, 2014a), the dynamics of the groundwater table Lana-Renault et al, 2014a), translocation and stemflow processes (SerranoMuela et al, 2012) and the hydrological properties of their soils (Seeger and Ries, 2008;Regüés et al, 2012Regüés et al, , 2017Serrano-Muela et al, 2014). These findings have enhanced knowledge of the runoff generation processes operating in these catchments under different rainfall and moisture conditions , 2014cSerrano-Muela et al, 2008;Nadal-Romero et al, 2016).…”
Section: The Catchmentsmentioning
confidence: 99%
“…Así, se ha estudiado su funcionamiento hidrológico (García-Ruiz et al, 2005;LanaRenault et al, 2007a, b), las propiedades físico-químicas de los suelos (Navas et al, 2002a(Navas et al, , b, 2005Seeger et al, 2004) y los procesos erosión y transporte de sedimentos (Lana-Renault y Regüés, 2007Regüés, , 2009López-Vicente et al, 2011).…”
Section: Figura 2 Características Principales De La Cuenca De Arnás:unclassified